Geometrical and graphic validation for patient management selection criteria in dental arches asymmetry - E. G. Vedeshina; D. A. Domenyuk; S. V. Dmitrienko; Zh. S. Orfanova (Кубанский научный медицинский вестник, 2015)
In this paper we propose a selection criterion that is applicable for the treatment of patients with dental arch asymmetry caused by loss of a premolar on one side of the mouth. According to a given criterion, the correlation between tooth size and dental arch parameters is determined. When applying this criterion for finding the correlation, the frontal distal diagonal size of the dental arch was multiplied by 1.14 coefficient. The sum of the mesio-distal diameters of seven teeth in the half-arc was subtracted from the obtained value. The value which was equal to 0±1.0 mm indicated the correlation between tooth size and dental arch parameters. We can conclude if there is correlation between tooth size and dental arch parameters, it is advisable to provide treatment associated with having the post-extraction socket opened and implant therapy performed (most commonly with the use of intraosseous dental implants).